Scientists as prophets - Walsh, Lynda (Oxford University Press, 2013)
Ebook from Oxford Scholarship Online; Includes bibliographical references (pages 201-259) and index; Prelude: scientists as prophets and the rhetoric of prophecy -- The Delphic oracle and ancient prophetic ethos -- The natural magician and the prophet: Francis Bacon's ethical alchemy -- Confirming signs: the prophetic ethos of the early Royal Society -- Interlude: competing ethical models and a catch-22 -- J. Robert Oppenheimer: cultic prophet -- Rachel Carson, kairotic prophet -- Media, metaphor, and the "oracles of science" -- Climate change and the technologies of prophecy -- Postlude: problems and solutions